Pentameric Ligand-Gated Ion Channels as Pharmacological Targets Against Chronic Pain - Lara, César O.; Burgos, Carlos F.; Moraga-Cid, Gustavo; Carrasco, Mónica A.; Yévenes, Gonzalo E. (Frontiers in Pharmacology, 2020)
Chronic pain is a common detrimental condition that affects around 20% of the world population. The current drugs to treat chronic pain states, especially neuropathic pain, have a limited clinical efficiency and present significant adverse effects that complicates their regular use. Recent studies have proposed new therapeutic strategies focused on the pharmacological modulation of G-protein-coupled receptors, transporters, enzymes and ion channels expressed on the nociceptive pathways. The present work intends to summarize recent advances on the pharmacological modulation of pentameric ligand-gated ion channels, which plays a key role in pain processing. Experimental data have shown that novel allosteric modulators targeting the excitatory nicotinic acetylcholine receptor, as well as the inhibitory GABAA and glycine receptors, reverse chronic pain-related behaviors in preclinical assays. Collectively, these evidences strongly suggest the pharmacological modulation of pentameric ligand-gated ion channels is a promising strategy towards the development of novel therapeutics to treat chronic pain states in humans.